Advanced textile engineering materials - Ul-Islam, Shahid; Butola, B.S. (Bhupendra Sing) (Hoboken, New Jersey : John Wiley & Sons, Inc. ; Salem, Massachusetts : Scrivener Publishing LLC, 2018)
"Advanced Textile Engineering Materials is written to educate readers about the use of advanced materials in various textile applications. In the first part, the book addresses recent advances in chemical finishing, and also highlights environmental issues in textile sectors. In the second part, the book provides a compilation of innovative fabrication strategies frequently adopted for the mechanical finishing of textiles. Market description: The book is written for readers from diverse backgrounds such as textile chemistry, textile engineering, and materials sciences"--
7.1 Introduction7.2 Global Competitors for Making Aerostat/Airship at Present; 7.3 Working Atmosphere of Aerostats and High Altitude Airship (HAA); 7.4 Materials Used in LTA Envelopes; 7.5 Case Studies on Different Coated or Laminated LTA Envelopes; 7.6 Advanced Polymer Nanocomposites as Potential Material for LTA Envelopes; 7.7 Models for Predicting the Performance and Service Life of Aerostats/Airships; 7.8 Challenges and Future Scopes; 7.9 Conclusion; References; Chapter 8: Woolen Carpet Industry: Environmental Impact and Recent Remediation Approaches; 8.1 Introduction
Description based on print version record and CIP data provided by publisher; resource not viewed.
Includes bibliographical references and index.
Keywords: Textile fabrics; TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING / Textiles & Polymers; Textile fabrics; Electronic books